GELAR MARIA BUNDA GEREJA Observasi Historis Dan Teologis - Janggat, Hilarius (LOGOS, 2009)
The second Vatican Council was not in favor of giving Mother Mary the title â€œMother of the Churchâ€, because of its absence in the New Testament and its scarcely using in Church Fathers. And of course this new title could hurt the separated brothers. But when council was going on, Pope Paul VI personally declared Blessed Virgin Mary as Mother of the Church, a truth of faith that has to be accepted and known by all the faithful. The title Mother of the Church substantially refers to Maryâ€™s spiritual motherhood for the whole Christian people, both faithful and pastors. She has manifested and exercised this role since her â€˜Yesâ€™ in the mystery of incarnation, her intercession in Cana, and her presence in Calvary. By calling the Blessed Virgin Mary Mother of the Church, Paul VI surpasses the hesitation of council fathers. This declaration, however, is not a dogma, but an ordinary Magisterium of the pope. By this action Paul VI indicates that the exercise of the pontificate Magisterium does not finish in the council.